THE EFFECT OF CHOOSING THE RIGHT EXERCISES IN LANGUAGE TEACHING (TAMADDUN NURI JURNALI, 2025)
This article examines the importance of choosing exercises correctly in the language teaching process and its impact on learning effectiveness. It analyzes how the appropriate selection of exercises plays a decisive role in the effective development of language skills (listening, speaking, reading and writing). It also highlights the types of exercises that are suitable for different learning stages and goals, as well as their didactic foundations.